Bacterial infections in alcoholic and nonalcoholic liver cirrhosis. Issue 9 (September 2015) - Sargenti, Konstantina; Prytz, Hanne; Nilsson, Emma; Bertilsson, Sara; Kalaitzakis, Evangelos
Abstract : Objectives: Longitudinal, population-based data on the occurrence, localization, and severity of bacterial infections over time in patients with alcoholic compared with nonalcoholic cirrhosis are limited. Materials and methods: All patients with incident cirrhosis diagnosed in 2001–2010 (area of 600 000 inhabitants) were retrospectively identified. All bacterial infections resulting in or occurring during an inpatient hospital episode during this period were registered. The etiology of cirrhosis (alcoholic vs. nonalcoholic), infection localization, and outcome as well as bacterial resistance patterns were analyzed. Patients were followed until death, transplant, or the end of 2011. Results: In all, 633 cirrhotics (363 alcoholic, 270 nonalcoholic) experienced a total of 398 infections (2276 patient-years). Among patients diagnosed with cirrhosis each year from 2001 to 2010, increasing trends were noted in the occurrence of infection (from 13 to 27%, P <0.001) and infection-related in-hospital mortality (from 2 to 7%, P =0.05), the latter mainly in the alcoholic group. Although alcoholic etiology was related to the occurrence of more frequent infection (Kaplan–Meier, P <0.001), this relationship was not significant after adjustment for confounders in Cox regression analysis ( P =0.056). Resistance to piperacilin-tazobactam and carbapenems was more common in infections occurring in alcoholic versus nonalcoholic cirrhosis (13 vs. 5%, P =0.057 and 12 vs. 2%, P =0.009). Alcoholic etiology predicted pneumonia and infections caused by Gram-positive bacteria in multivariate analysis ( P <0.05 for both). Conclusion: In a population-based cirrhotic cohort, bacterial infections increased over time, which, in the case of alcoholic cirrhosis, was associated with pneumonia and bacterial resistance to antibiotics. However, alcoholic etiology was not related indepedently to the occurrence of bacterial infections. Abstract : Supplemental Digital Content is available in the text.